Is Freedom A Debate In Africa? A Re-Examination of the Existential Precepts of Freedom and Authenticity in Africa - Udisi, Ebikisei Stanley (dialektika kontemporer, 2024)
This research investigates the complicated and contentious idea of freedom in Africa, focusing on the existential principles of freedom, authenticity, and responsibility within the continent's distinct historical, cultural, and philosophical settings. Drawing on Jean-Paul Sartre's existentialist precepts, this study examines the contradictions between individual freedom and community values, emphasizing the need for a comprehensive understanding of African existentialism. The history of colonialism, imperialism, and ne-ocolonialism has affected Africa's perception of independence, raising concerns about authenticity and self-determination. This research contends that embracing freedom and authenticity is critical for Africans to regain their identity, encourage self-determination, and generate true growth. By interacting with African philosophers such as Kwame Gyekye and Kwasi Wiredu, this study adds to continuing discussions about freedom, authenticity, and responsibility in African cultures.